Drenagem pleuro-amniótica. - Carla T Rodrigues; Paula Maciel; Sónia C Ribeiro; Carlos L Carvalho; Joaquim P Correia; Luís F Matos; José B Mesquita; Ana B Couceiro; Fernanda R Jardim (Acta Médica Portuguesa, 2005)
Fetal hydrothorax refers to a collection of fluid within the fetal thorax that may be the result of chylous leak from the thoracic duct (primary hydrothorax) or generalized fluid retention associated with immune or no immune fetal hydrops (secondary hydrothorax). The authors' presents a case report occurred in 2002, of a pregnant woman that at 25 weeks' gestation that was referred to Maternidade Bissaya-Barreto-Coimbra because of a fetal hydrothorax at left, under tension and with cardiac decompensation signs. A fetal thoracocentesis was performed and the diagnosis was chylothorax. Because of a rapid reaccumulation of fluid a pleuroamniotic shunt was placed. The effusion and the cardiac decompensation signs regressed. The delivery was at 38 weeks' gestation. The newborn had been stable. Actually he has 10 months, is healthy and has a normal grow and development.